Gait and Conditioned Fear Impairments in a Mouse Model of Comorbid TBI and PTSD. (20th September 2018) - Teutsch, Peyton; Jones, Carolyn E.; Kaiser, Mara E.; Avalon Gardner, Natasha; Lim, Miranda M.
Abstract : Study Objectives . Traumatic brain injury (TBI) and posttraumatic stress disorder (PTSD) commonly cooccur. Approaches to research and treatment of these disorders have been segregated, despite overlapping symptomology. We and others have hypothesized that comorbid TBI + PTSD generates worse symptoms than either condition alone. We present a mouse model of comorbid TBI + PTSD to further explore this condition. Methods . A mouse model of TBI + PTSD was generated using the single prolonged stress (SPS) protocol in combination with the controlled cortical impact (CCI) protocol. This resulted in four experimental groups: control, TBI, PTSD, and TBI + PTSD. Behavioral phenotyping included gait analysis, contextual fear conditioning, acoustic startle response, and prepulse inhibition. Results . Mice in the TBI + PTSD group showed a significantly impaired gait compared to their counterparts with TBI alone as well as control mice. Mice in the TBI + PTSD group showed significantly impaired contextual fear recall compared to controls. Prepulse inhibition testing revealed intact acoustic startle and auditory sensory gating. Conclusions . These results indicate that SPS paired with CCI in mice produces unique behavioral impairments in gait and fear recall that are not present in either condition alone. Further studies are underway to examine additional behavioral, physiological, and pathological phenotypes in this combined model of TBI + PTSD.